3x-3=2x-9

Simple and best practice solution for 3x-3=2x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-3=2x-9 equation:


Simplifying
3x + -3 = 2x + -9

Reorder the terms:
-3 + 3x = 2x + -9

Reorder the terms:
-3 + 3x = -9 + 2x

Solving
-3 + 3x = -9 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-3 + 3x + -2x = -9 + 2x + -2x

Combine like terms: 3x + -2x = 1x
-3 + 1x = -9 + 2x + -2x

Combine like terms: 2x + -2x = 0
-3 + 1x = -9 + 0
-3 + 1x = -9

Add '3' to each side of the equation.
-3 + 3 + 1x = -9 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = -9 + 3
1x = -9 + 3

Combine like terms: -9 + 3 = -6
1x = -6

Divide each side by '1'.
x = -6

Simplifying
x = -6

See similar equations:

| 4x-10y=100 | | 2y+6y=48 | | 3(x+17)=5 | | -120=8x | | 2-3k=10 | | 6x+4+2x=42 | | -4z-7+12z=37-12 | | 6x+6=11x-24 | | 12-x=9 | | 6x+6=-34-4x | | 24=2m | | 2x+[x+3]=24 | | 33.7-(1.5s+2.3)=3.4-(0.4-5.7s) | | 5+4p=-7 | | 5x+4=x+20 | | -6z+4(z+3)=-2z+14 | | 6x+141=5x-3 | | XY+Y= | | -13+13=0 | | 5x-2(4+4x)=11 | | -4(4+7n)+5(3+4n)=-5n-2n | | a^4-7a^2+10=0 | | 9x-8=3x+4 | | 165+20x=180 | | -6n=2m+3 | | -4(4+7n)+5(3+4n)=-5-2n | | 15v-9v=42 | | y=-2(5)+2 | | x+2x+[x+3]=23 | | y-11=-27 | | 17x-10x=-6 | | 10z-6=4z-15-3z |

Equations solver categories